CN121574435A - A sodium hyaluronate gel microsphere, its preparation method and application - Google Patents

A sodium hyaluronate gel microsphere, its preparation method and application

Info

Publication number
CN121574435A
CN121574435A CN202610112911.6A CN202610112911A CN121574435A CN 121574435 A CN121574435 A CN 121574435A CN 202610112911 A CN202610112911 A CN 202610112911A CN 121574435 A CN121574435 A CN 121574435A
Authority
CN
China
Prior art keywords
sodium hyaluronate
preparation
hyaluronate gel
crosslinking
gel
Prior art date
Legal status (The legal status is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the status listed.)
Pending
Application number
CN202610112911.6A
Other languages
Chinese (zh)
Inventor
贾毅凡
廖泳
魏灵钰
徐嘉鑫
Current Assignee (The listed assignees may be inaccurate. Google has not performed a legal analysis and makes no representation or warranty as to the accuracy of the list.)
Xiangtan Sumei Medical Technology Co ltd
Original Assignee
Xiangtan Sumei Medical Technology Co ltd
Priority date (The priority date is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the date listed.)
Filing date
Publication date
Application filed by Xiangtan Sumei Medical Technology Co ltd filed Critical Xiangtan Sumei Medical Technology Co ltd
Priority to CN202610112911.6A priority Critical patent/CN121574435A/en
Publication of CN121574435A publication Critical patent/CN121574435A/en
Pending legal-status Critical Current

Links

Classifications

    • C—CHEMISTRY; METALLURGY
    • C08—ORGANIC MACROMOLECULAR COMPOUNDS; THEIR PREPARATION OR CHEMICAL WORKING-UP; COMPOSITIONS BASED THEREON
    • C08B—POLYSACCHARIDES; DERIVATIVES THEREOF
    • C08B37/00—Preparation of polysaccharides not provided for in groups C08B1/00 - C08B35/00; Derivatives thereof
    • C08B37/006—Heteroglycans, i.e. polysaccharides having more than one sugar residue in the main chain in either alternating or less regular sequence; Gellans; Succinoglycans; Arabinogalactans; Tragacanth or gum tragacanth or traganth from Astragalus; Gum Karaya from Sterculia urens; Gum Ghatti from Anogeissus latifolia; Derivatives thereof
    • C08B37/0063—Glycosaminoglycans or mucopolysaccharides, e.g. keratan sulfate; Derivatives thereof, e.g. fucoidan
    • C08B37/0072—Hyaluronic acid, i.e. HA or hyaluronan; Derivatives thereof, e.g. crosslinked hyaluronic acid (hylan) or hyaluronates
    • A—HUMAN NECESSITIES
    • A61—MEDICAL OR VETERINARY SCIENCE; HYGIENE
    • A61L—METHODS OR APPARATUS FOR STERILISING MATERIALS OR OBJECTS IN GENERAL; DISINFECTION, STERILISATION OR DEODORISATION OF AIR; CHEMICAL ASPECTS OF BANDAGES, DRESSINGS, ABSORBENT PADS OR SURGICAL ARTICLES; MATERIALS FOR BANDAGES, DRESSINGS, ABSORBENT PADS OR SURGICAL ARTICLES
    • A61L27/00—Materials for grafts or prostheses or for coating grafts or prostheses
    • A61L27/14—Macromolecular materials
    • A61L27/20—Polysaccharides
    • A—HUMAN NECESSITIES
    • A61—MEDICAL OR VETERINARY SCIENCE; HYGIENE
    • A61L—METHODS OR APPARATUS FOR STERILISING MATERIALS OR OBJECTS IN GENERAL; DISINFECTION, STERILISATION OR DEODORISATION OF AIR; CHEMICAL ASPECTS OF BANDAGES, DRESSINGS, ABSORBENT PADS OR SURGICAL ARTICLES; MATERIALS FOR BANDAGES, DRESSINGS, ABSORBENT PADS OR SURGICAL ARTICLES
    • A61L27/00—Materials for grafts or prostheses or for coating grafts or prostheses
    • A61L27/50—Materials characterised by their function or physical properties, e.g. injectable or lubricating compositions, shape-memory materials, surface modified materials
    • A—HUMAN NECESSITIES
    • A61—MEDICAL OR VETERINARY SCIENCE; HYGIENE
    • A61L—METHODS OR APPARATUS FOR STERILISING MATERIALS OR OBJECTS IN GENERAL; DISINFECTION, STERILISATION OR DEODORISATION OF AIR; CHEMICAL ASPECTS OF BANDAGES, DRESSINGS, ABSORBENT PADS OR SURGICAL ARTICLES; MATERIALS FOR BANDAGES, DRESSINGS, ABSORBENT PADS OR SURGICAL ARTICLES
    • A61L27/00—Materials for grafts or prostheses or for coating grafts or prostheses
    • A61L27/50—Materials characterised by their function or physical properties, e.g. injectable or lubricating compositions, shape-memory materials, surface modified materials
    • A61L27/52—Hydrogels or hydrocolloids
    • A—HUMAN NECESSITIES
    • A61—MEDICAL OR VETERINARY SCIENCE; HYGIENE
    • A61L—METHODS OR APPARATUS FOR STERILISING MATERIALS OR OBJECTS IN GENERAL; DISINFECTION, STERILISATION OR DEODORISATION OF AIR; CHEMICAL ASPECTS OF BANDAGES, DRESSINGS, ABSORBENT PADS OR SURGICAL ARTICLES; MATERIALS FOR BANDAGES, DRESSINGS, ABSORBENT PADS OR SURGICAL ARTICLES
    • A61L27/00—Materials for grafts or prostheses or for coating grafts or prostheses
    • A61L27/50—Materials characterised by their function or physical properties, e.g. injectable or lubricating compositions, shape-memory materials, surface modified materials
    • A61L27/58—Materials at least partially resorbable by the body
    • C—CHEMISTRY; METALLURGY
    • C08—ORGANIC MACROMOLECULAR COMPOUNDS; THEIR PREPARATION OR CHEMICAL WORKING-UP; COMPOSITIONS BASED THEREON
    • C08J—WORKING-UP; GENERAL PROCESSES OF COMPOUNDING; AFTER-TREATMENT NOT COVERED BY SUBCLASSES C08B, C08C, C08F, C08G or C08H
    • C08J3/00—Processes of treating or compounding macromolecular substances
    • C08J3/02—Making solutions, dispersions, lattices or gels by other methods than by solution, emulsion or suspension polymerisation techniques
    • C08J3/03—Making solutions, dispersions, lattices or gels by other methods than by solution, emulsion or suspension polymerisation techniques in aqueous media
    • C08J3/075—Macromolecular gels
    • C—CHEMISTRY; METALLURGY
    • C08—ORGANIC MACROMOLECULAR COMPOUNDS; THEIR PREPARATION OR CHEMICAL WORKING-UP; COMPOSITIONS BASED THEREON
    • C08J—WORKING-UP; GENERAL PROCESSES OF COMPOUNDING; AFTER-TREATMENT NOT COVERED BY SUBCLASSES C08B, C08C, C08F, C08G or C08H
    • C08J3/00—Processes of treating or compounding macromolecular substances
    • C08J3/12—Powdering or granulating
    • A—HUMAN NECESSITIES
    • A61—MEDICAL OR VETERINARY SCIENCE; HYGIENE
    • A61L—METHODS OR APPARATUS FOR STERILISING MATERIALS OR OBJECTS IN GENERAL; DISINFECTION, STERILISATION OR DEODORISATION OF AIR; CHEMICAL ASPECTS OF BANDAGES, DRESSINGS, ABSORBENT PADS OR SURGICAL ARTICLES; MATERIALS FOR BANDAGES, DRESSINGS, ABSORBENT PADS OR SURGICAL ARTICLES
    • A61L2400/00—Materials characterised by their function or physical properties
    • A61L2400/06—Flowable or injectable implant compositions
    • C—CHEMISTRY; METALLURGY
    • C08—ORGANIC MACROMOLECULAR COMPOUNDS; THEIR PREPARATION OR CHEMICAL WORKING-UP; COMPOSITIONS BASED THEREON
    • C08J—WORKING-UP; GENERAL PROCESSES OF COMPOUNDING; AFTER-TREATMENT NOT COVERED BY SUBCLASSES C08B, C08C, C08F, C08G or C08H
    • C08J2305/00—Characterised by the use of polysaccharides or of their derivatives not provided for in groups C08J2301/00 or C08J2303/00
    • C08J2305/08—Chitin; Chondroitin sulfate; Hyaluronic acid; Derivatives thereof

Landscapes

  • Health & Medical Sciences (AREA)
  • Chemical & Material Sciences (AREA)
  • Medicinal Chemistry (AREA)
  • Life Sciences & Earth Sciences (AREA)
  • General Health & Medical Sciences (AREA)
  • Public Health (AREA)
  • Epidemiology (AREA)
  • Transplantation (AREA)
  • Animal Behavior & Ethology (AREA)
  • Oral & Maxillofacial Surgery (AREA)
  • Dermatology (AREA)
  • Veterinary Medicine (AREA)
  • Dispersion Chemistry (AREA)
  • Chemical Kinetics & Catalysis (AREA)
  • Polymers & Plastics (AREA)
  • Organic Chemistry (AREA)
  • Molecular Biology (AREA)
  • Engineering & Computer Science (AREA)
  • Biochemistry (AREA)
  • Materials Engineering (AREA)
  • Pharmaceuticals Containing Other Organic And Inorganic Compounds (AREA)

Abstract

本发明公开了一种透明质酸钠凝胶微球及其制备方法和应用,属于生物医用材料领域。本发明请求保护一种透明质酸钠凝胶微球,该透明质酸钠凝胶微球由透明质酸通过自交联形成,交联键为酯键;该透明质酸钠凝胶微球的溶胀度范围为12.5~70.9,粒径范围为2.8~2000μm。本发明透明质酸钠凝胶微球依靠透明质酸自交联形成,催化交联反应使用的碳二亚胺衍生物或N‑羟基琥珀酰亚胺衍生物完成催化后不与透明质酸钠以化学键连接,可通过清洗从产物中移除,降低交联剂不良反应风险,还可以兼顾高模量与快降解,得到的球形状态的透明质酸钠凝胶产品易于注射使用,特别适合用作短期硬质填充材料。

This invention discloses a sodium hyaluronate gel microsphere, its preparation method, and its application, belonging to the field of biomedical materials. This invention claims protection for a sodium hyaluronate gel microsphere, which is formed by self-crosslinking of hyaluronic acid, with the crosslinking bond being an ester bond; the swelling degree of the sodium hyaluronate gel microsphere ranges from 12.5 to 70.9, and the particle size ranges from 2.8 to 2000 μm. The sodium hyaluronate gel microsphere of this invention relies on the self-crosslinking of hyaluronic acid. The carbodiimide derivative or N-hydroxysuccinimide derivative used in the catalytic crosslinking reaction does not chemically bond with sodium hyaluronate after catalysis, and can be removed from the product by washing, reducing the risk of adverse reactions from the crosslinking agent. It also balances high modulus and rapid degradation. The resulting spherical sodium hyaluronate gel product is easy to inject and is particularly suitable as a short-term rigid filler material.

Description

Sodium hyaluronate gel microsphere and preparation method and application thereof
Technical Field
The invention belongs to the field of biomedical materials, and relates to sodium hyaluronate gel, in particular to sodium hyaluronate gel microspheres, and a preparation method and application thereof.
Background
Hyaluronic Acid (HA) is a polymer in which acetylglucosamine and glucuronic acid are alternately bonded via glycosidic bonds, and is often present in the form of sodium salt. HA is a polysaccharide naturally occurring in connective tissue of the human body, HAs good biocompatibility, water retention and viscoelasticity, and is widely used in the medical and cosmetic fields such as skin filling, soft tissue repair, joint lubrication, etc.
The non-crosslinked HA is easy to be degraded by HA enzyme in vivo, HAs low mechanical strength, and limits the application of the non-crosslinked HA in long-acting filling and shaping, so that a crosslinking agent is often used to enable the HA to form a gel network, the degradation resistance is improved, and the mechanical properties (such as modulus) of the gel are improved. Meanwhile, in various HA gel forms, spherical particles are favored because of round appearance, lower tissue irritation, and smaller rolling resistance (easy injection) of the spherical particles.
The cross-linking agent of HA may be selected from a variety of cross-linking agents such as DVS (divinyl sulfone, national standard 20203130096), BDDE (1, 4-butanediol glycidyl ether, national standard 20193130257), lysine (national standard 20243131239) and PEG (polyethylene glycol, national standard 20253130825). With the progress of crosslinking technology, the safety of the crosslinking agent itself has been improved, but as a foreign substance, the crosslinking agent always has a risk of causing adverse reactions such as allergy.
In addition, the crosslinked HA gel may have a higher modulus (achieving a hard filling effect) than the uncrosslinked HA, and the higher the degree of crosslinking, the higher the modulus. However, the degradation time of the gel is also increased due to the increase of the crosslinking degree, so that the HA gel cannot be obtained in both the short degradation period and the high modulus, and the application of the HA gel in the field of short-term hard filling (such as tissue engineering repair of a stent, postoperative anti-adhesion, joint filling and the like) is limited.
The invention provides the preparation method for the HA gel microsphere, which aims to solve the problems that the crosslinking agent of the HA gel microsphere in the prior art is allergic in risk and cannot be simultaneously degraded in a short period and high in modulus.
Disclosure of Invention
The invention aims to overcome the defects of the prior art, and the first aim is to provide a sodium hyaluronate gel microsphere, the second aim is to provide a preparation method of the sodium hyaluronate gel microsphere, and the third aim is to provide an application of the sodium hyaluronate gel microsphere in preparing a medical filling material.
The above object of the present invention is achieved by the following technical scheme:
the sodium hyaluronate gel microsphere is formed by self-crosslinking hyaluronic acid, a crosslinking bond is an ester bond, the swelling degree of the sodium hyaluronate gel microsphere ranges from 12.5 to 70.9, and the particle size range is 2.8 to 2000 mu m.
The preparation method of the sodium hyaluronate gel microsphere comprises the following steps:
Step S1, dissolving hyaluronic acid or salt thereof and a catalyst in a solvent A to obtain an aqueous phase solution;
s2, dissolving a tackifier in the solvent B to obtain an oil phase solution;
Step S3, mixing the aqueous phase solution and the oil phase solution, and performing suspension polymerization to obtain the aqueous phase solution and the oil phase solution after the reaction is finished;
Wherein:
In the step S1, the catalyst consists of carbodiimide derivatives and N-hydroxysuccinimide derivatives, wherein a group of glucuronic acid and acetamido glucose in hyaluronic acid or salts thereof are recorded as a repeating unit, the mass ratio of the repeating unit in the hyaluronic acid or salts thereof to the substances of the carbodiimide derivatives and the N-hydroxysuccinimide derivatives is 1 (0.3-1.5): 0.15-2.25), the solvent A is one or more selected from water, physiological saline and phosphate buffer solution, the molecular weight of the hyaluronic acid or salts thereof is 40 kDa-1000 kDa, and the concentration of the hyaluronic acid or salts thereof in an aqueous solution is 5-22 wt%;
In the step S2, the tackifier is selected from one or more of cellulose acetate butyrate, cellulose acetate propionate, ethyl cellulose, polymethyl methacrylate, polystyrene and polyvinyl butyral, and the solvent B is selected from organic solvents which are not mutually soluble with water.
Preferably, in step S1, the carbodiimide derivative is selected from one or more of 1-ethyl-3- (3-dimethylaminopropyl) carbodiimide hydrochloride, N ' -dicyclohexylcarbodiimide, N ' -diisopropylcarbodiimide, N-cyclohexyl-N ' - (2-morpholinoethyl) carbodiimide mesylate.
Preferably, in step S1, the N-hydroxysuccinimide derivative is selected from one or more of N-hydroxysuccinimide, N-hydroxysulfosuccinimide sodium salt, N-hydroxysulfosuccinimide.
Preferably, in step S1, the pH of the aqueous solution is in the range of 4.55-6.95.
Preferably, in step S2, the solvent B is selected from one or more of butyl acetate, amyl acetate, hexyl acetate, butyl propionate, butyl butyrate, dimethyl carbonate, diethyl carbonate.
Preferably, in the step S2, the concentration of the tackifier in the oil phase solution is 0.5 to 15wt.%.
Preferably, in the step S3, the volume ratio of the aqueous phase solution to the oil phase solution is 1:1-40.
Preferably, in the step S3, the suspension polymerization temperature is 10-90 ℃, the reaction time is 0.5-24 h, and the stirring rotation speed is 200-1500 rpm.
The sodium hyaluronate gel microsphere or the application of the sodium hyaluronate gel microsphere prepared by any one of the preparation methods in the preparation of medical filling materials.
The beneficial effects are that:
1. the sodium hyaluronate gel microsphere provided by the invention is formed by self-crosslinking of hyaluronic acid, and the carbodiimide derivative or the N-hydroxysuccinimide derivative used for catalyzing the crosslinking reaction is not connected with sodium hyaluronate by chemical bonds after catalysis, so that the sodium hyaluronate gel microsphere can be removed from a product by cleaning, and the adverse reaction risk of a crosslinking agent is reduced;
2. The hyaluronic acid in the sodium hyaluronate gel microsphere provided by the invention is crosslinked through ester bonds, the gel modulus is obviously improved due to the increase of the crosslinking degree, and the degradation period variation range is smaller, so that the sodium hyaluronate gel microsphere can be simultaneously and rapidly degraded, and is particularly suitable for being used as a short-term hard filling material;
3. Compared with the prior art (such as CN 111647193A for obtaining spongy sodium hyaluronate gel), the preparation method provided by the invention can obtain a spherical sodium hyaluronate gel product by a suspension polymerization method, and the spherical sodium hyaluronate gel product has small rolling resistance among spherical particles and is easy to inject.
The generation mechanism of the beneficial effects is as follows:
1. Mechanism for reducing adverse reaction risk of crosslinked product
Carbodiimide derivatives and N-hydroxysuccinimide derivatives are a group of catalysts that can activate carboxyl groups, with glucuronic acid units in HA bearing carboxyl groups, which can be activated. The glucuronic acid and the acetamido glucose both contain hydroxyl groups, and the activated carboxyl groups can react with the hydroxyl groups to form ester bonds, namely, HA and HA are crosslinked, and a crosslinking agent is not required to be additionally introduced. The specific chemical reaction is shown in the following formula (EDC/NHS is taken as an example).
;
The ester bond in the HA crosslinked by the ester bond can be broken by hydrolysis, and the glycosidic bond of glucuronic acid and acetylglucosamine in the HA is not influenced by the ester bond, and can be hydrolyzed (or enzymatically hydrolyzed). The cross-linking agent fragments will not be released after degradation, and therefore there is no cross-linking agent related safety risk. In contrast to the crosslinking agents (such as BDDE) used in the prior art, the crosslinking agents are directly connected with HA molecules during crosslinking to form a chemical bond connecting structure such as HA-BDDE-HA, and the chemical bond connecting structure cannot be removed through cleaning, so that the crosslinking agent molecules are inevitably released after the gel is degraded in a human body, and the risk of adverse reactions related to the crosslinking agents is brought.
2. The mechanism of high modulus and quick degradation is considered
The traditional crosslinking agents BDDE, DVS, lysine and the like crosslink HA gel, wherein the crosslinking bonds are ether bonds and amide bonds, and the chemical bonds have strong hydrolysis resistance. The network pore size of the crosslinked HA gel is small, and the HA enzyme such macromolecular proteins are not allowed to permeate, and the gel can only be degraded from the surface. Therefore, the cross-link hydrolysis and HA enzymolysis paths are considered at the same time, and the enzymolysis paths are the rate-determining steps for the overall degradation of the gel. With the improvement of the crosslinking degree, the enzymolysis resistance of the gel is obviously improved, and the comprehensive degradation time of the gel is obviously improved with the improvement of the crosslinking degree under the in-vivo environment of the simultaneous occurrence of hydrolysis and enzymolysis.
In contrast, the HA gel disclosed in the present invention is crosslinked via an ester bond, which is a readily hydrolyzable chemical bond. The size of the water molecules is smaller than the network pores of the gel, and all chemical bonds in the gel are hydrolyzed simultaneously after the gel is contacted with water. Thus, the hydrolysis pathway is the rate-determining step for the overall degradation of the gel. Even by increasing the degree of crosslinking, the number of ester bonds is increased (while improving the mechanical properties of the gel), since hydrolysis of the ester bonds within the gel occurs simultaneously (water molecules can penetrate the gel network) rather than starting from the surface of the gel particles, the degradation cycle of the gel is less correlated with the degree of crosslinking. Further, the crosslinking degree is improved, the modulus of the gel can be obviously improved, but the degradation time is not obviously increased, and the combination of quick degradation and high modulus of the gel is realized.
3. Mechanism of obtaining spherical sodium hyaluronate gel by suspension polymerization
The rolling resistance among the spherical particles is small and easy to inject, and the irregular particles are in the structures such as bulges and depressions, so that the injection difficulty is high. The disclosed technology (CN 111647193A) is easy to generate porous and foaming structures during the synthesis of block HA gel, and the inventor researches that a small amount of isocyanate (carbodiimide derivative synthesis raw material) is inevitably remained in the production process of the carbodiimide derivative, and carbon dioxide is generated after the isocyanate reacts with water, so that the foaming crosslinked HA is foamed. According to the invention, the aqueous phase solution is dispersed into micron-sized liquid drops, so that carbon dioxide is easy to diffuse and separate from gel, and the crosslinked HA which is compact, round and free of holes can be formed.
Drawings
FIG. 1 is an optical micrograph of the product of example 1 (A) after reconstitution with physiological saline, the product of example 1 (B) as dry powder, and the product of comparative example 1 (C) after reconstitution with physiological saline.
FIG. 2 shows the storage modulus test results of the products of examples 1, 4, 6 and 7.
FIG. 3 is an infrared spectrum of the product prepared in example 7 and its raw materials.
FIG. 4 is a graph showing particle size distribution of the products prepared in examples 7 to 10
Detailed Description
The following describes the essential aspects of the present invention in detail with reference to examples, but those skilled in the art will recognize that the scope of the present invention should not be limited to the specific examples.
1. Preparation of sodium hyaluronate gel microspheres
Example 1:
Step S1, HA (hyaluronic acid, the same applies hereinafter) with molecular weight of 100 kDa is dissolved in deionized water to form a solution with concentration of 10 wt percent. After adjusting pH to 4.8.+ -. 0.05 with 0.1M HCl/NaOH, EDC and NHS were added as a 1-ethyl-3- (3-dimethylaminopropyl) carbodiimide hydrochloride (hereinafter also NHS (N-hydroxysuccinimide, hereinafter also referred to as N-hydroxysuccinimide) =1:0.5:0.5 (molar ratio) to the HA repeating unit (one group of glucuronic acid and acetamido glucose was referred to as one repeating unit), and the mixture was stirred at room temperature to obtain a homogeneous solution as an aqueous phase.
Step S2, dissolving cellulose acetate butyrate in butyl acetate to form a solution with the concentration of 5 wt percent, wherein the solution is used as an oil phase.
And S3, adding 50 mL water phase into 500 mL oil phase under the mechanical stirring of 10 ℃ and 1000 rpm, carrying out suspension polymerization for 24h, centrifuging after the reaction is finished, collecting microspheres, dialyzing sequentially with an oil phase solvent and absolute ethyl alcohol, and drying to obtain the product.
Example 2:
Step S1, dissolving HA with a molecular weight of 200 kDa in deionized water to form a solution with a concentration of 8: 8 wt. After adjusting the pH to 4.8.+ -. 0.05 with 0.1M HCl/NaOH, EDC and NHS were added in a molar ratio of HA repeating unit: EDC: NHS=1:0.5:0.5, and stirred at room temperature to give a homogeneous solution as an aqueous phase.
The other steps were the same as in example 1.
Example 3:
Step S1, dissolving HA with molecular weight of 500 kDa in deionized water to form a solution with concentration of 5 wt%. After adjusting the pH to 4.8.+ -. 0.05 with 0.1M HCl/NaOH, EDC and NHS were added in a molar ratio of HA repeating unit: EDC: NHS=1:0.5:0.5, and stirred at room temperature to give a homogeneous solution as an aqueous phase.
The other steps were the same as in example 1.
Example 4:
Step S1, dissolving HA with molecular weight of 100 kDa in deionized water to form a solution with concentration of 10 wt%. After adjusting the pH to 4.8.+ -. 0.05 with 0.1M HCl/NaOH, EDC and NHS were added in a molar ratio of HA repeating unit: EDC: NHS=1:0.3:0.3, and stirred at room temperature to give a homogeneous solution as an aqueous phase.
The other steps were the same as in example 1.
Example 5:
Step S1, dissolving HA with the molecular weight of 1000 kDa in deionized water to form a solution with the concentration of 5wt percent. After adjusting the pH to 4.8.+ -. 0.05 with 0.1M HCl/NaOH, EDC and NHS were added in a molar ratio of HA repeating unit: EDC: NHS=1:0.5:0.5, and stirred at room temperature to give a homogeneous solution as an aqueous phase.
The other steps were the same as in example 1.
Example 6:
Step S1, dissolving HA with molecular weight of 100 kDa in deionized water to form a solution with concentration of 10 wt%. After adjusting the pH to 4.8.+ -. 0.05 with 0.1M HCl/NaOH, EDC and NHS were added in a molar ratio of HA repeating unit: EDC: NHS=1:1.0:1.0, and stirred at room temperature to give a homogeneous solution as an aqueous phase.
The other steps were the same as in example 1.
Example 7:
Step S1, HA with molecular weight of 100 kDa is dissolved in deionized water to form a solution with concentration of 10 wt percent. After adjusting the pH to 4.8.+ -. 0.05 with 0.1M HCl/NaOH, EDC and NHS were added in a molar ratio of HA repeating unit: EDC: NHS=1:1.5:1.5, and stirred at room temperature to give a homogeneous solution as an aqueous phase.
The other steps were the same as in example 1.
Example 8:
Step S1, HA with molecular weight of 40 kDa is dissolved in physiological saline to form a solution with concentration of 6 wt percent. After adjusting pH to 4.6.+ -. 0.05 with 0.1M HCl/NaOH, DCC and NHS (N, N' -dicyclohexylcarbodiimide) were added as HA repeating units (NHS=1:0.3:0.15) (molar ratio), and the mixture was stirred at room temperature to give a homogeneous solution as a water phase.
Step S2, dissolving cellulose acetate propionate in amyl acetate to form a solution with the concentration of 0.5 wt percent as an oil phase.
And S3, adding 50mL water phase into 50mL oil phase under mechanical stirring at 90 ℃ and 1500 rpm, carrying out suspension polymerization to obtain 0.5h, centrifuging after the reaction is finished, collecting microspheres, dialyzing with an oil phase solvent and absolute ethyl alcohol in sequence, and drying to obtain the product.
Example 9:
Step S1, HA with the molecular weight of 150 kDa is dissolved in normal saline to form a solution with the concentration of 22: 22 wt. After adjusting pH to 6.5.+ -. 0.05 with 0.5M HCl/KOH, DIC (N, N' -diisopropylcarbodiimide, hereinafter also referred to as "Sulfo-NHS") was added as the repeating unit of HA in a molar ratio of DIC to Sulfo-NHS (N-hydroxysulfosuccinimide sodium salt, hereinafter also referred to as "1:1:1.5", and the mixture was stirred at room temperature to give a homogeneous solution as an aqueous phase.
And S2, dissolving polymethyl methacrylate in dimethyl carbonate to form a solution with the concentration of 15 wt percent as an oil phase.
And S3, adding 50mL water phase into 2000 mL oil phase under mechanical stirring at 40 ℃ and 200 rpm, carrying out suspension polymerization for 4h, centrifuging after the reaction is finished, collecting microspheres, dialyzing sequentially with an oil phase solvent and absolute ethyl alcohol, and drying to obtain the product.
Example 10:
Step S1, HA with a molecular weight of 150 kDa is dissolved in phosphate buffer solution to form a solution with a concentration of 5 wt percent. After adjusting pH to 6.9.+ -. 0.05 with 0.5M phosphoric acid/KOH, CMC (N-cyclohexyl-N' - (2-morpholinoethyl) carbodiimide mesylate, hereinafter also NHSS (N-hydroxysulfosuccinimide, hereinafter also) in a molar ratio of 1:1.5:2.25 was added to CMC and NHSS and stirred at room temperature to give a homogeneous solution as aqueous phase.
Step S2, dissolving polyvinyl butyral in butyl butyrate to form a solution with the concentration of 12 wt percent, and taking the solution as an oil phase.
And S3, adding 50 mL water phase into 1000 mL oil phase under the mechanical stirring of 650 rpm at 60 ℃ for suspension polymerization of 2h, centrifuging to collect microspheres after the reaction is finished, dialyzing with oil phase solvent and absolute ethyl alcohol in sequence, and drying to obtain the product.
Comparative example 1 (differing from example 1 in the concentration of HA):
Step S1, dissolving HA with molecular weight of 100 kDa in deionized water to form a solution with concentration of 4: 4 wt%. After adjusting the pH to 4.8.+ -. 0.05 with 0.1M HCl/NaOH, EDC and NHS were added in a molar ratio of HA repeating unit: EDC: NHS=1:0.5:0.5, and stirred at room temperature to give a homogeneous solution as an aqueous phase.
The other steps were the same as in example 1.
Comparative example 2 (differing from example 2 in the concentration of HA):
Step S1, dissolving HA with a molecular weight of 200 kDa in deionized water to form a solution with a concentration of 4: 4 wt. After adjusting the pH to 4.8.+ -. 0.05 with 0.1M HCl/NaOH, EDC and NHS were added in a molar ratio of HA repeating unit: EDC: NHS=1:0.5:0.5, and stirred at room temperature to give a homogeneous solution as an aqueous phase.
The other steps were the same as in example 1.
Comparative example 3 (differing from example 3 in the concentration of HA):
Step S1, dissolving HA with molecular weight of 500 kDa in deionized water to form a solution with concentration of 2 wt%. After adjusting the pH to 4.8.+ -. 0.05 with 0.1M HCl/NaOH, EDC and NHS were added in a molar ratio of HA repeating unit: EDC: NHS=1:0.5:0.5, and stirred at room temperature to give a homogeneous solution as an aqueous phase.
The other steps were the same as in example 1.
Comparative example 4 (differing from example 4 in the ratio of HA repeat units to EDC, NHS):
Step S1, dissolving HA with molecular weight of 100 kDa in deionized water to form a solution with concentration of 10 wt%. After adjusting the pH to 4.8.+ -. 0.05 with 0.1M HCl/NaOH, EDC and NHS were added in a molar ratio of HA repeating unit: EDC: NHS=1:0.2:0.2, and stirred at room temperature to give a homogeneous solution as an aqueous phase.
The other steps were the same as in example 1.
2. Performance testing
1. Microsphere formability
(1) Test sample
The products prepared in examples 1-3 and comparative examples 1-3 of the invention.
(2) Test item
Microcosmic morphology, namely adding physiological saline into a sample to be detected and observing the sample under a microscope.
(3) Test results
As shown in Table 1, not all concentrations of the solutions can be suspension polymerized to give spherical products. As shown in fig. 1 (bottom left) which shows the microscopic morphology of the product of example 1, the product can be seen as fine irregular particles. After reconstitution with physiological saline, the product of example 1 swells into spherical gel particles (on fig. 1). However, the product of comparative example 1 was greatly different from the product of example 1 in terms of morphology before swelling with physiological saline, but it was not maintained in the form of spherical particles after addition of physiological saline, but was directly dissolved in physiological saline to form flocculent floats (lower right in FIG. 1).
;
(4) Analysis of results
The carbodiimide derivative and the N-hydroxysuccinimide derivative form intermediates which are highly reactive in catalyzing the activation of carboxyl groups and can be consumed by hydroxyl groups in water, i.e. the hydroxyl groups in HA and the hydroxyl groups in aqueous solution need to compete for reaction with the activated carboxyl groups in HA. When the concentration of HA in the reaction system is sufficiently low, the number of crosslinks formed by the reaction is insufficient, i.e., the degree of crosslinking is insufficient. Therefore, the gel particles obtained after crosslinking cannot withstand the swelling effect of water molecules and break, and cannot maintain the spherical morphology.
The products obtained in examples 2 to 10 have a similar spheronizability as the product obtained in example 1.
2. Degree of crosslinking and related Properties
(1) Test sample
The products prepared in examples 1, 4, 6, 7 and comparative example 4 of the present invention.
(2) Test item
Swelling degree, namely weighing a sample to be measured, and marking the mass as m1. Adding the product into sufficient physiological saline to fully swell, taking out the swelled gel, wiping free water on the surface, weighing, and marking the mass as m2. The swelling degree was (m 2-m 1)/m 1.
Storage modulus, namely adding a sample to be tested into sufficient physiological saline to fully swell, and removing free water outside the gel microspheres. Gel microspheres were placed on a plate rotor of a rheometer at an experimental temperature of 25 ℃ with a constant strain of 1%, tiled thickness of 1mm, 25mm plate rotor, and the results at 0.1 Hz.
And (3) hydrolyzing, namely adding the sample to be tested into sufficient physiological saline to fully swell, and placing the sample at 70 ℃ to accelerate the hydrolysis. Every 0.5 h observations were made, with no gelatinous particles seen in the solution as hydrolysis endpoint.
And (3) performing enzymolysis, namely taking a 50 mg sample to be detected, and adding 5 mL of 50U/mL of sodium hyaluronate enzyme physiological saline solution. And (3) carrying out enzymolysis at 37 ℃ after uniform oscillation, observing every 1h, and taking gel particles which cannot be observed under a microscope as an enzymolysis end point.
Adding sufficient physiological saline into a sample to be tested for redissolution, sucking the redissolved gel microspheres into a 1 mL syringe, standing, pushing out free water, and setting the pushing speed to be 30mm/min by using a 27G needle.
(3) Test results
As shown in table 2, the properties of the crosslinked HA gel microspheres with different catalyst amounts were significantly characterized.
;
(4) Analysis of results
The crosslinking density and mechanical property are that as the molar ratio of HA repeating units to EDC to NHS is increased from 1:0.3:0.3 (example 4) to 1:1.5:1.5 (example 7), the swelling degree is reduced from 70.9 to 12.5, the storage modulus is increased from 58 Pa to 3.410 Pa (as shown in figure 2), and the promotion is about 59 times, so that the ester bond crosslinking network can realize gradient high-modulus regulation on the premise of no external crosslinking agent. The swelling degree of the products obtained in examples 1 to 10 is in the range of 12.5 to 70.9.
Degradation rate-degree of crosslinking weak coupling-hydrolysis time is prolonged from 4 h to 11 h (less than 3 times), enzymolysis time is prolonged from 5 h to 74 h (about 15 times), and modulus rise amplitude is significantly lower (59 times). The 'weak coupling' phenomenon verifies the core effect of the 'high modulus-fast degradation' of the invention, and the mechanism is that ester bonds are 'easy hydrolysis bonds', water molecules can penetrate through the whole micro-net and break at the same time, but not surface-centripetal layer-by-layer degradation is performed, even if the crosslinking degree is greatly improved, the whole hydrolysis time is still short, and the enzymolysis time is not the step of the whole degradation of the material.
The injectability is that the maximum pushing force of the spheronizable sample is less than or equal to 5N and is far lower than the threshold value of 'comfortable pushing' of a clinically common 27G needle head (about 10N), and the pushing force is not obviously increased along with the increase of the crosslinking degree, so that the round microsphere still keeps the advantage of 'low rolling resistance' under the 'high modulus' state.
The gel formed in comparative example 4 (molar ratio 1:0.2:0.2) has too low a crosslinking density and still has a strong flowability, and the mechanical and degradation properties cannot be tested, further proving that a sufficient crosslinking level is a necessary condition for ensuring spherical gel particles, consistent with the conclusion of "microsphere formability".
3. Infrared spectrum
(1) Test sample
The product obtained in example 7.
(2) Test item
The detection is carried out according to four 0402 infrared spectrophotometry methods in Chinese pharmacopoeia (2020 edition).
(3) Test results
The infrared spectrum of example 7 and the raw materials used therein is shown in FIG. 3.
(4) Analysis of results
Since the infrared characteristics of the products prepared in each example were almost identical, analysis was performed using the representative profile of example 7 (high crosslinking level).
Sodium Hyaluronate (HA) is a polysaccharide whose main infrared characteristic peaks include about 3400 cm -1: O-H stretching vibration (hydroxy group) and about 2900 cm -1: C-H stretching vibration (methylene and methine groups on sugar ring). About 1650 cm -1 and about 1550 cm -1 amide I and amide II bands (from N-acetylglucosamine units). These peaks are observed in both the HA starting material and the gel microspheres. Meanwhile, the infrared peak shape of the HA raw material and the gel microsphere are basically consistent, which indicates that the composition of the gel microsphere is almost HA.
At the same time, however, some of the characteristic peaks of the HA raw material were changed compared to the gel microspheres. For example, about 1600 cm -1 and about 1410 cm -1 (shown as #1 and # 2) the asymmetric and symmetric stretching vibrations of carboxylic acid, the gel microspheres showed a significant decrease in the relative peak intensity, indicating a decrease in the number of carboxyl groups of the gel microspheres relative to the HA starting material, and about 1100-1000 cm -1 (shown as # 3) the C-O-C and C-O stretching vibrations (glycosidic bond and hydroxyl group), the gel microspheres showed a decrease in the relative peak intensity, indicating a decrease in the number of carboxyl groups of the gel microspheres relative to the HA starting material. In addition, the gel microsphere was newly added with a characteristic peak at about 1700 cm -1 (denoted as #4 in the figure) relative to the HA raw material, which was attributed to the stretching vibration peak of the carbonyl group on the ester bond.
The intensity change and the new increase of the infrared peak show that the components of the gel microsphere are still HA. After crosslinking, the amount of carboxyl groups and hydroxyl groups is reduced, and ester bonds are formed.
Taken together, it is shown that gel microspheres are formed by self-crosslinking of ester bonds.
4. Microsphere particle size
(1) Test sample
The products prepared in examples 7 to 10 of the present invention.
(2) Test item
Particle size is determined by adding physiological saline into sample to be measured to reach steady state, and wet-method determination according to the third method (light scattering method) of particle size and particle size distribution determination method of 0982 of pharmacopoeia of the people's republic of China (four parts) (2020 edition).
(3) Test results
Particle size distribution diagrams of the products prepared in examples 7 to 10 are shown in FIG. 4, and particle size statistics are shown in Table 3.
;
(4) Analysis of results
The particle size distribution of the gel microspheres is controlled by parameters such as molecular weight concentration, water-oil ratio and the like, and the microspheres with the size of 2.8-2000 mu m can be prepared. Screening the product can also result in a narrower particle size distribution based on the particle size of the resulting product. The particle sizes of the products obtained in examples 1 to 10 are all in the range of 2.8 to 2000. Mu.m.
It can be seen that, in summary:
1. The sodium hyaluronate gel microsphere provided by the invention is formed by self-crosslinking of hyaluronic acid, and carbodiimide derivatives or N-hydroxysuccinimide derivatives connected with sodium hyaluronate through chemical bonds cannot exist in the product, so that the adverse reaction risk is reduced;
2. The hyaluronic acid in the sodium hyaluronate gel microsphere provided by the invention is crosslinked through ester bonds, the gel modulus is obviously improved due to the increase of the crosslinking degree, and the degradation period variation range is smaller, so that the sodium hyaluronate gel microsphere can be simultaneously and rapidly degraded, and is particularly suitable for being used as a short-term hard filling material;
3. Compared with the prior art (such as CN 111647193A for obtaining spongy sodium hyaluronate gel), the preparation method provided by the invention can obtain a spherical sodium hyaluronate gel product by a suspension polymerization method, and the spherical sodium hyaluronate gel product has small rolling resistance among spherical particles and is easy to inject.
The above-described embodiments serve to describe the substance of the present invention in detail, but those skilled in the art should understand that the scope of the present invention should not be limited to this specific embodiment.

Claims (10)

1.一种透明质酸钠凝胶微球,其特征在于:所述透明质酸钠凝胶微球由透明质酸通过自交联形成,交联键为酯键;所述透明质酸钠凝胶微球的溶胀度范围为12.5~70.9,粒径范围为2.8~2000μm。1. A sodium hyaluronate gel microsphere, characterized in that: the sodium hyaluronate gel microsphere is formed by self-crosslinking of hyaluronic acid, wherein the crosslinking bond is an ester bond; the swelling degree of the sodium hyaluronate gel microsphere ranges from 12.5 to 70.9, and the particle size ranges from 2.8 to 2000 μm. 2.一种如权利要求1所述透明质酸钠凝胶微球的制备方法,其特征在于,包括以下步骤:2. A method for preparing sodium hyaluronate gel microspheres as described in claim 1, characterized in that it comprises the following steps: 步骤S1、将透明质酸或其盐与催化剂溶解在溶剂A中,得到水相溶液;Step S1: Dissolve hyaluronic acid or its salt and the catalyst in solvent A to obtain an aqueous solution; 步骤S2、将增粘剂溶解在溶剂B中,得到油相溶液;Step S2: Dissolve the thickener in solvent B to obtain an oil phase solution; 步骤S3、将水相溶液与油相溶液混合,进行悬浮聚合,反应结束后即得;Step S3: Mix the aqueous solution and the oil solution, and carry out suspension polymerization. The product is obtained after the reaction is completed. 其中:in: 步骤S1中,所述催化剂由碳二亚胺衍生物和N-羟基琥珀酰亚胺衍生物组成;以透明质酸或其盐中一组葡萄糖醛酸与乙酰氨基葡萄糖记为一个重复单元,透明质酸或其盐中重复单元与碳二亚胺衍生物、N-羟基琥珀酰亚胺衍生物的物质的量之比为1:(0.3~1.5):(0.15~2.25);所述溶剂A选自水、生理盐水、磷酸盐缓冲液中的一种或多种;所述透明质酸或其盐的分子量为40 kDa~1000kDa,其在水相溶液中的浓度为5 ~ 22wt.%;In step S1, the catalyst is composed of a carbodiimide derivative and an N-hydroxysuccinimide derivative; a repeating unit is defined as a group of glucuronic acid and acetylglucosamine in hyaluronic acid or its salts, and the molar ratio of the repeating unit in hyaluronic acid or its salts to the carbodiimide derivative and the N-hydroxysuccinimide derivative is 1:(0.3~1.5):(0.15~2.25); the solvent A is selected from one or more of water, physiological saline, and phosphate buffer; the molecular weight of the hyaluronic acid or its salts is 40 kDa~1000 kDa, and its concentration in the aqueous solution is 5~22 wt.%. 步骤S2中,所述增粘剂选自乙酸丁酸纤维素、乙酸丙酸纤维素、乙基纤维素、聚甲基丙烯酸甲酯、聚苯乙烯、聚乙烯醇缩丁醛中的一种或多种;所述溶剂B选自与水不互溶的有机溶剂。In step S2, the thickener is selected from one or more of cellulose acetate butyrate, cellulose acetate propionate, ethyl cellulose, polymethyl methacrylate, polystyrene, and polyvinyl butyral; the solvent B is selected from organic solvents that are immiscible with water. 3.根据权利要求2所述的制备方法,其特征在于:步骤S1中,所述碳二亚胺衍生物选自1-乙基-3-(3-二甲氨基丙基)碳二亚胺盐酸盐、N,N'-二环己基碳二亚胺、N,N'-二异丙基碳二亚胺、N-环己基-N'-(2-吗啉乙基)碳二亚胺甲磺酸盐中的一种或多种。3. The preparation method according to claim 2, characterized in that: in step S1, the carbodiimide derivative is selected from one or more of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, N,N'-dicyclohexylcarbodiimide, N,N'-diisopropylcarbodiimide, and N-cyclohexyl-N'-(2-morpholinoethyl)carbodiimide methanesulfonate. 4.根据权利要求2所述的制备方法,其特征在于:步骤S1中,所述N-羟基琥珀酰亚胺衍生物选自N-羟基琥珀酰亚胺、N-羟基硫代琥珀酰亚胺钠盐、N-羟基磺基琥珀酰亚胺中的一种或多种。4. The preparation method according to claim 2, characterized in that: in step S1, the N-hydroxysuccinimide derivative is selected from one or more of N-hydroxysuccinimide, sodium N-hydroxythiosuccinimide, and N-hydroxysulfosuccinimide. 5.根据权利要求2所述的制备方法,其特征在于:步骤S1中,水相溶液的pH范围为4.55~ 6.95。5. The preparation method according to claim 2, characterized in that: in step S1, the pH range of the aqueous solution is 4.55~6.95. 6.根据权利要求2所述的制备方法,其特征在于:步骤S2中,溶剂B选自乙酸丁酯、乙酸戊酯、乙酸己酯、丙酸丁酯、丁酸丁酯、碳酸二甲酯、碳酸二乙酯中的一种或多种。6. The preparation method according to claim 2, characterized in that: in step S2, solvent B is selected from one or more of butyl acetate, amyl acetate, hexyl acetate, butyl propionate, butyl butyrate, dimethyl carbonate, and diethyl carbonate. 7.根据权利要求2所述的制备方法,其特征在于:步骤S2中,所述增粘剂在油相溶液中的浓度为0.5 ~ 15wt.%。7. The preparation method according to claim 2, characterized in that: in step S2, the concentration of the thickener in the oil phase solution is 0.5 ~ 15 wt.%. 8.根据权利要求2所述的制备方法,其特征在于:步骤S3中,水相溶液与油相溶液的体积比为1:1 ~ 40。8. The preparation method according to claim 2, characterized in that: in step S3, the volume ratio of the aqueous phase solution to the oil phase solution is 1:1 to 40. 9.根据权利要求2所述的制备方法,其特征在于:步骤S3中,悬浮聚合的温度为10 ~ 90℃,反应时间为0.5 ~ 24 h,搅拌转速为200 ~ 1500 rpm。9. The preparation method according to claim 2, characterized in that: in step S3, the temperature of suspension polymerization is 10 ~ 90℃, the reaction time is 0.5 ~ 24 h, and the stirring speed is 200 ~ 1500 rpm. 10.权利要求1所述的透明质酸钠凝胶微球或权利要求2~9任一制备方法制备的透明质酸钠凝胶微球在制备医用填充材料中的应用。10. The application of the sodium hyaluronate gel microspheres according to claim 1 or the sodium hyaluronate gel microspheres prepared by any of the preparation methods of claims 2 to 9 in the preparation of medical filler materials.
CN202610112911.6A 2026-01-27 2026-01-27 A sodium hyaluronate gel microsphere, its preparation method and application Pending CN121574435A (en)

Priority Applications (1)

Application Number Priority Date Filing Date Title
CN202610112911.6A CN121574435A (en) 2026-01-27 2026-01-27 A sodium hyaluronate gel microsphere, its preparation method and application

Applications Claiming Priority (1)

Application Number Priority Date Filing Date Title
CN202610112911.6A CN121574435A (en) 2026-01-27 2026-01-27 A sodium hyaluronate gel microsphere, its preparation method and application

Publications (1)

Publication Number Publication Date
CN121574435A true CN121574435A (en) 2026-02-27

Family

ID=98841777

Family Applications (1)

Application Number Title Priority Date Filing Date
CN202610112911.6A Pending CN121574435A (en) 2026-01-27 2026-01-27 A sodium hyaluronate gel microsphere, its preparation method and application

Country Status (1)

Country Link
CN (1) CN121574435A (en)

Citations (7)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
CN103816573A (en) * 2014-03-01 2014-05-28 湖南科技大学 Preparation method of porous gelatin/hyaluronic acid composite microspheres
CN104231285A (en) * 2013-06-09 2014-12-24 冯淑芹 Hyaluronic acid derivative gel and preparing method thereof
CN108264581A (en) * 2017-02-20 2018-07-10 上海昊海生物科技股份有限公司 A kind of self-crosslinking Sodium Hyaluronate and preparation method thereof
CN111632198A (en) * 2020-06-24 2020-09-08 四川大学 A kind of self-crosslinking hyaluronic acid and gelatin composite hydrogel injection and its preparation method and application
CN111647193A (en) * 2020-06-24 2020-09-11 华熙生物科技股份有限公司 Method for improving self-crosslinking degree of hyaluronic acid and obtained hyaluronic acid self-crosslinking product
CN118483351A (en) * 2024-05-31 2024-08-13 渼颜空间(河北)生物科技有限公司 Method for detecting DMTMM residue in crosslinked gel containing hyaluronic acid or salt thereof as monomer
CN121059898A (en) * 2025-08-28 2025-12-05 中国科学院宁波材料技术与工程研究所 Self-crosslinking hyaluronic acid microsphere without exogenous crosslinking agent and preparation method thereof

Patent Citations (7)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
CN104231285A (en) * 2013-06-09 2014-12-24 冯淑芹 Hyaluronic acid derivative gel and preparing method thereof
CN103816573A (en) * 2014-03-01 2014-05-28 湖南科技大学 Preparation method of porous gelatin/hyaluronic acid composite microspheres
CN108264581A (en) * 2017-02-20 2018-07-10 上海昊海生物科技股份有限公司 A kind of self-crosslinking Sodium Hyaluronate and preparation method thereof
CN111632198A (en) * 2020-06-24 2020-09-08 四川大学 A kind of self-crosslinking hyaluronic acid and gelatin composite hydrogel injection and its preparation method and application
CN111647193A (en) * 2020-06-24 2020-09-11 华熙生物科技股份有限公司 Method for improving self-crosslinking degree of hyaluronic acid and obtained hyaluronic acid self-crosslinking product
CN118483351A (en) * 2024-05-31 2024-08-13 渼颜空间(河北)生物科技有限公司 Method for detecting DMTMM residue in crosslinked gel containing hyaluronic acid or salt thereof as monomer
CN121059898A (en) * 2025-08-28 2025-12-05 中国科学院宁波材料技术与工程研究所 Self-crosslinking hyaluronic acid microsphere without exogenous crosslinking agent and preparation method thereof

Similar Documents

Publication Publication Date Title
CN102070786B (en) Hyaluronic acid-sodium alginate composite hydrogel and preparation method thereof
CN111848991B (en) Preparation method of crosslinked hyaluronic acid microspheres
Rinaudo Main properties and current applications of some polysaccharides as biomaterials
US8536317B2 (en) Crosslinked polysaccharide sponge
EP1587945B1 (en) Hydroxyphenyl cross-linked macromolecular network and applications thereof
CN105473622B (en) Method for making shaped cross-linked hyaluronic acid product
CN110964215B (en) Preparation method of L-polylactic acid and cross-linked hyaluronic acid composite gel for injection and obtained product
US9872827B2 (en) Cross-linked sodium hyaluronate gel for tissue filler for plastic surgery and preparation method thereof
Li et al. In vitro and in vivo evaluation of 3D biodegradable thermo/pH sensitive sol-gel reversible hydroxybutyl chitosan hydrogel
Shen et al. pH and redox dual stimuli-responsive injectable hydrogels based on carboxymethyl cellulose derivatives
Onyianta et al. The effects of morpholine pre-treated and carboxymethylated cellulose nanofibrils on the properties of alginate-based hydrogels
CN110003360A (en) The method for being used to prepare the hyaluronic acid product of crosslinking
CN107383397B (en) Hyaluronic acid derivative self-crosslinking hydrogel taking oxidized hydroxyethyl cellulose as crosslinking agent and preparation method thereof
CN108853569A (en) A kind of covalent cross-linking hyaluronic acid aeroge and its hydrogel and preparation method
CN114470330B (en) Recombinant collagen gel particles for tissue filling and preparation method thereof
CA2518806C (en) Photocrosslinked-polysaccharide composition and production process of the same
CN110408057A (en) Suitable for biomedical DHPMC blended cross linking modified collagen and preparation method thereof
CN119731257A (en) Hydrogels for soft tissue filling
CN116903884A (en) Hyaluronic acid-polyglutamic acid hydrogel and preparation method thereof
Rashidi et al. Polymerization of chondroitin sulfate and its stimulatory effect on cartilage regeneration; a bioactive material for cartilage regeneration
CN108264581A (en) A kind of self-crosslinking Sodium Hyaluronate and preparation method thereof
CN121059898A (en) Self-crosslinking hyaluronic acid microsphere without exogenous crosslinking agent and preparation method thereof
KR102532697B1 (en) A method of preparing polymeric micro particles, polymeric micro particles, medical composition, cosmetic composition, medical articles and cosmetic articles using the same
Deng et al. Preparation and characterization of hyaluronan/chitosan scaffold cross‐linked by 1‐ethyl‐3‐(3‐dimethylaminopropyl) carbodiimide
CN114206996A (en) Method for producing polymer microparticles, medical composition, cosmetic composition, medical article, and cosmetic article using same

Legal Events

Date Code Title Description
PB01 Publication
PB01 Publication
SE01 Entry into force of request for substantive examination
SE01 Entry into force of request for substantive examination